A guide to naming human non‐coding RNA genes - Seal, RL; Chen, L; Griffiths‐Jones, S; Lowe, TM; Mathews, MB; O'Reilly, D; Pierce, AJ; Stadler, PF; Ulitsky, I; Wolin, SL; Bruford, EA (EMBO Press, 2020)
Research on non‐coding RNA (ncRNA) is a rapidly expanding field. Providing an official gene symbol and name to ncRNA genes brings order to otherwise potential chaos as it allows unambiguous communication about each gene. The HUGO Gene Nomenclature Committee (HGNC, www.genenames.org) is the only group with the authority to approve symbols for human genes. The HGNC works with specialist advisors for different classes of ncRNA to ensure that ncRNA nomenclature is accurate and informative, where possible. Here, we review each major class of ncRNA that is currently annotated in the human genome and describe how each class is assigned a standardised nomenclature.